2008
DOI: 10.1097/shk.0b013e3180ca9e53
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of the Urinary Concentration Defect and Effect of Desmopressin During Endotoxemia in Rats

Abstract: Acute renal failure during human sepsis is often nonoliguric. To study the underlying mechanisms, renal function was assessed in endotoxic and control male Wistar rats during and after saline loading and treatment with the selective V2 receptor agonist desmopressin. Escherichia coli endotoxin (dose, 8 mg/kg) was administered from time (t)=0 to t=60 min; saline loading (rate, 5 mL/100 g per hour) was administered from t=0 to t=120 min. Thereafter, half of each group received desmopressin (dose, 10 microg) for 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
1
11
1
Order By: Relevance
“…In this study, an increased UO and water clearance were clearly observed using an intraperitoneal endotoxin challenge despite an AVP osmotic pump infusion, which induced a tenfold higher induced AVP plasma concentration. Importantly, this model demonstrated increased kidney AQP-2 apical membrane expression after LPS challenge, contrary to that observed in three studies (31, 32, 34), especially that of Versteilen et al (34) who localized reduced lumen AQP-2, but in a short-term intravenous and fluid-resuscitated model. In addition, AVP-induced enhanced daily urinary excretion of AQP-2, which represents nearly 4% of total kidney expression at baseline (36), was almost completely abolished by LPS challenge.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…In this study, an increased UO and water clearance were clearly observed using an intraperitoneal endotoxin challenge despite an AVP osmotic pump infusion, which induced a tenfold higher induced AVP plasma concentration. Importantly, this model demonstrated increased kidney AQP-2 apical membrane expression after LPS challenge, contrary to that observed in three studies (31, 32, 34), especially that of Versteilen et al (34) who localized reduced lumen AQP-2, but in a short-term intravenous and fluid-resuscitated model. In addition, AVP-induced enhanced daily urinary excretion of AQP-2, which represents nearly 4% of total kidney expression at baseline (36), was almost completely abolished by LPS challenge.…”
Section: Discussioncontrasting
confidence: 98%
“…This medulla-to-cortex microvascular redistribution is not necessarily apparent by measuring total RBF, and the associated reactivity to vasoconstrictor agents is either normal or increased (29-31). Several hours after challenge, endotoxemia in rats often causes polyuria (31, 32, 34). Indeed, as much as one third of sepsis-induced ARF are polyuric at bedside (33, 34), and when oliguric, acute tubular necrosis is generally suspected (5, 34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have documented that endotoxemia induced by lipopolysaccharide led to diuresis, downregulation of AQP2 (37,46), and an impaired V2R/AQP2 network as well (7,16), suggesting that proinflammatory cytokines may be involved in the regulation of AQP2 and urinary concentrating defects seen in endotoxemia. IL-1␤, a key proinflammatory cytokine, is produced by macrophages, monocytes, endothelial cells, tubular epithelial cells, and mesangial cells in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in a rat endotoxin model the V2 agonist desmopressin restored endotoxininduced decreases in sodium reabsorption, inner medulary osmolality and urine osmolality, while decreasing urine flow [52] , suggesting that V2 receptor stimulation plays a beneficial role. In contrast, in an animal model of sepsis which resulted in impaired renal function in the presence of vasopressin, V2 receptors appeared to mediate impaired creatinine clearance [53] .…”
Section: The Effects Of Vasopressin On Renal Functionmentioning
confidence: 99%